ISLAMIC ACCOUNTING: AN OVERVIEW OF IDEOLOGICAL INTERPRETATIONS - Agus Arwani (Indonesian Journal of Islamic Literature and Muslim Society)
The paper aims to explore the ideological interpretation of Islamic accounting. It is hoped that the results of various interpretations of Islamic accounting are obtained comprehensively. The research method used is qualitative research. Qualitative research is called Participant-Observation because the researcher himself must be the main instrument in collecting data by directly observing the object being examined While the research approach uses a literature study. The results of this study found that there are several views on the interpretation of Islamic accounting ideology. The fragile philosophical foundation of context knowledge is enough to create counter paradigm rivals as a consequence of the scientific revolution (science revolutions) in the form of an alternative paradigm shift due to the failure of the old paradigm to answer a set of problems. The content of the Islamic substance is liberation, making accounting perceived as a treatise